Description of Coleophora maculosa sp. nov. (Lepidoptera, Coleophoridae) from the Southern Ural Mountains - Šumpich, Jan; Richter, Ignác (Zootaxa, 2025)
In this paper, a new species of Coleophora Hübner, 1822 is described from Russia: Coleophora maculosa sp. nov. The holotype was collected on steppe habitat in the Southern Ural Mountains near the Ural River floodplain, an area with extensive floodplain forests. Photographs of adult specimen and genitalia are provided.